A New Worker Category under the Personal Service Income Regime in Australia - Allen, Christina (Thomson Reuters, 2021)
In the past, Australia's tax laws responded to the ever-changing legal environment within which businesses operate, while employing anti-avoidance provisions. Introduced in 2000, the tax regime known as "personal service income", which treats certain contractors and business owners/managers as employees, diverged from this approach. This article explores the factors driving the formulation of the regime and whether the pre-existing anti-avoidance provisions were ineffective. It finds that the regime was motivated by counterbalancing the fiscal impact of the proposed corporate tax rate reduction and consequently brought about a new category of workers who have all legal rights and obligations outside the existing tax laws as independent contractors but are treated as employees for tax purposes. These workers are akin to dependent contractors – which has no legal or commercial meaning in Australia. These findings indicate a potential opening for a new method of legislating tax laws.